The impact of using the imaginative learning strategy in teaching social and national education to develop critical thinking skills among sixth grade students in Saudi Arabia - Al Harthy, Saad Ayed Saad (Journal of Educational and Psychological Sciences, 2017)
The aim of this study was to investigate the effect of using the strategy of imagination in teaching social and national education on the development of critical thinking skills among sixth grade students in the Kingdom of Saudi Arabia. The study was followed by a semi-experimental method according to the design of a tribal type after the study. The sample of the study (50) of the students of the sixth grade of primary school (Prince Faisal primary for males) was chosen by the intentional method. The experimental group and the number of its members (25) students studied using the strategy of imagination, and the control group and the number of members (25) students studied in the usual way. In order to achieve the objectives of the study, the lessons of the seventh unit (development in the national) were rewritten in the book of social and national education for the sixth grade in accordance with the strategy of imagination, and used to answer the questions of the study test to measure the skills of critical thinking, where the results showed significant differences in the results of the test of critical thinking Between the applications of the tribal and the remote for the benefit of the post-application, as well as the existence of an impact to use the strategy of imagination in the development of critical thinking skills. .
Keywords: Imagination strategy; critical thinking; social and patriotic education; sixth grade